Treatment and Prognosis of Male Breast Cancer: A Multicentric, Retrospective Study Over 11 Years in the Czech Republic - Bielcikova, Zuzana; Holanek, Milos; Selingerova, Iveta; Sorejs, Ondrej; Kolarova, Iveta; Soumarova, Renata; Proks, Jan; Reifova, Lucie; Cmejlova, Vlastimila; Linkova, Lenka; Zabojnikova, Michaela; Chodacka, Martina; et al. (The oncologist, 2024)
PURPOSE: Male breast cancer (MBC) is a rare, but increasingly common disease, and lacks prospective studies. Collaborative efforts are needed to understand and address MBC, including its prognosis, in different countries. METHODS: We retrospectively reviewed the clinical, histopathological, and molecular-genetic characteristics, treatments, and survival outcomes of MBC diagnosed between 2007 and 2017 in the Czech Republic. Prognostic factors of overall survival (OS), recurrence-free interval (RFi), and breast cancer-specific mortality (BCSM) were analyzed and indirectly compared to international data. RESULTS: We analyzed 256 patients with MBC (median age 66 years), including 12% with de novo metastatic (M1). Of 201 non-metastatic (M0) patients, 6% were <40 years old, 29% had stage I, 55% were cN0, and 54% underwent genetic testing. Overall, 97% of tumors had estrogen receptor expression ≥10%, 61% had high Ki67 index, 40% were high-grade (G3), and 68% were luminal B-like (HER2-negative). Systemic therapies included endocrine therapy (90%) and chemotherapy (53%). Few (5%) patients discontinued adjuvant endocrine therapy for reasons other than disease relapse or death. Patients treated with aromatase inhibitors alone had significantly shorter RFi (P < .001). OS, RFi, and BCSM were associated with disease stage, T stage, N stage, progesterone receptor expression, grade, and Ki67 index. Median OS reached 122 and 42 months in M0 and de novo M1 patients, respectively. CONCLUSION: Due to the rarity of MBC, this study highlights important findings from real clinical practice. Although the number of patients with MBC with unfavorable features was higher in this Czech dataset than in international studies, the prognosis remains consistent with real-world evidence.
Keywords: senioři; senioři nad 80 let; prognosis; Retrospective Studies; Prognosis; Česká republika; Middle Aged; mužské pohlaví; epidemiology; Adult; Czech Republic; Aged, 80 and over; Breast Neoplasms, Male; prognóza; retrospektivní studie; Humans; nádory prsu u mužů; retrospective study; lidé středního věku; male breast cancer; dospělí; Aged; genetic testing; lidé; Male